Interfaces between Cranial Bone and AISI 304 Steel after Long-Term Implantation: A Case Study of Cranial Screws - Luptáková, Natália; Dlouhý, Václav; Sobola, Dinara; Fintová, Stanislava; Weiser, Adam; Beneš, Vladimír; Dlouhý, Antonín (ACS biomaterials science & engineering, 2024)
Interfaces between AISI 304 stainless steel screws and cranial bone were investigated after long-term implantation lasting for 42 years. Samples containing the interface regions were analyzed using state-of-the-art analytical techniques including secondary ion mass, Fourier-transform infrared, Raman, and X-ray photoelectron spectroscopies. Local samples for scanning transmission electron microscopy were cut from the interface regions using the focused ion beam technique. A chemical composition across the interface was recorded in length scales covering micrometric and nanometric resolutions and relevant differences were found between peri-implant and the distant cranial bone, indicating generally younger bone tissue in the peri-implant area. Furthermore, the energy dispersive spectroscopy revealed an 80 nm thick steel surface layer enriched by oxygen suggesting that the AISI 304 material undergoes a corrosion attack. The attack is associated with transport of metallic ions, namely, ferrous and ferric iron, into the bone layer adjacent to the implant. The results comply with an anticipated interplay between released iron ions and osteoclast proliferation. The interplay gives rise to an autocatalytic process in which the iron ions stimulate the osteoclast activity while a formation of fresh bone resorption sites boosts the corrosion process through interactions between acidic osteoclast extracellular compartments and the implant surface. The autocatalytic process thus may account for an accelerated turnover of the peri-implant bone.
Keywords: železo; Bone Screws; Humans; povrchové vlastnosti; Iron; Photoelectron Spectroscopy; fotoelektronová spektroskopie; koroze; Skull; rozhraní kost/implantát; Ramanova spektroskopie; stainless steel AISI 304; Corrosion; nerezavějící ocel; lidé; kostní šrouby; implant; spektroskopie infračervená s Fourierovou transformací; Spectroscopy, Fourier Transform Infrared; Spectrum Analysis, Raman; Stainless Steel; peri-implant bone; biocorrosion; lebka; Bone-Implant Interface; Surface Properties; remodelling